HUBUNGAN KARAKTERISTIK LINGKUNGAN FISIK RUMAH DAN PERILAKU DENGAN KEJADIAN TB PARU DI WILAYAH KERJA PUSKESMAS BOBOTSARI KABUPATEN PURBALINGGA - Anggi Fathrida Nuraini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis which typically affects the lungs (pulmonary tuberculosis). Prevalence of Pulmonary tuberculosis in Bobotsari Sub-district was the highest in Purbalingga Regency since 2009-2012. Prevalence of Pulmonary tuberculosis in Bobotsari Sub-district in 2013 was 16,2/10.000. This research’s design is case control study to acknowledge the environmental health factors in housing and behaviours assosiated with Pulmonary tuberculosis in Bobotsari Primary Health Care District of Purbalingga Regency. The subject of this study is 66 respondent consist of 33 cases and 33 controls with purposive sampling as the method’s. Data analyzis done by chi square test, with 95% level of significance and 5% degree of error. The results showed that five variables assosiated with pulmonary Tuberculosis are unqualified floor type (p-value=0,027; OR=3,640), unqualified ceiling (p-value =0,001; OR=6,720), bad habit of drying mattres (p-value=0,026; OR=3,121), malnutrition status (p-value=0,0001; OR=26,667), and no history of BCG immunization status (p-value=0,024; OR=3,200). The conclusion of this research is that the unqualified floor type, unqualified ceiling, bad habit of drying mattress, malnutrition status, and no history of BCG immunization status are the risk factors of pulmonary tuberculosis.